Alcida Rita Ramos. Una vida de compromiso con la etnografía y con los pueblos indígenas - Luis Cayón (Journal de la Société des Américanistes)
This text presents Alcida Rita Ramos’ personal, professional and academic trajectory. It highlights certain crucial moments in her biography to better understand her thinking and contributions to Americanist Anthropology. The text highlights her research projects and her political commitment to the Yanomami people. It covers the various phases of her career and reveals some of her recent thoughts on the future of ethnography and anthropology, which stress the importance of the new surge of indigenous anthropologists in Brazilian universities.